The Concept of Ma‘arifa in Sufism as a Pathway to Spiritual Realization in Islamic Mysticism - Dr. Humaira Khalil; Dr. Mubashirah; Dr. Arif Hussain (`, 2025)
The concept of Ma‘arifa in Sufism represents a profound journey toward spiritual enlightenment and inner realization of the Divine. Rooted in Islamic mysticism, Ma‘arifa goes beyond conventional knowledge, serving as an experiential form of divine understanding that touches the heart and soul of the seeker. This research delves into Ma‘arifa as a critical aspect of the Sufi path, emphasizing its role in attaining a deeper awareness of Allah. Unlike intellectual knowledge, which is acquired through study, Ma‘arifa is attained through purification of the self (nafs), remembrance of God (dhikr), and divine unveiling (kashf). The paper explores the sources of Ma‘arifa, including the Qur’an, the Hadith of the Prophet Muhammad (PBUH), spiritual guidance from Murshids, and the inner experiences of the seeker. It further highlights the significance of the heart (qalb) in Sufi thought as the ultimate receptacle for this profound knowledge. By examining the stages of spiritual progression, from outer practices (Shari’ah) to the inner journey (Tariqah) and ultimate truth (Haqiqah), this research underscores Ma‘arifa as a transformative force that leads the believer closer to Allah, bringing about humility, compassion, and an intimate connection with the Divine. Ultimately, Ma‘arifa serves as a pathway to spiritual realization, guiding the Sufi towards a life of peace, sincerity, and divine love. Keywords: Ma‘arifa, Sufism, Islamic Mysticism, Spiritual Realization, Divine Knowledge, Dhikr, Kashf, Tariqah, Haqiqah, Sufi Path, Heart (Qalb).